Insektisida Rumah Tangga dan Keberadaan Larva Aedes aegypti di Jakarta Selatan - Mutiara Widawati; Nurul Hidayati kusumastuti (ASPIRATOR - Journal of Vector-borne Disease Studies, 2017)
There are many research about household insecticides, however research about the effect of household insecticide active ingredients to the presence of larvae has never been optimized yet. There are some people in Indonesia who think that to avoid mosquito bites simply can be done by only using insecticides. Some types of insecticides has been used since long time ago to control mosquitoes in households, but until now, research about mosquitoes control by insecticides is limited to adult mosquitoes only. Research about the effect of household insecticide active ingredients to the presence of larvae has never been done. Therefore, this study aims to determine the relationship between the various content of the insecticide to the presence of larvae in South Jakarta as densely populated area. 300 household were used as samples, data about the use of insecticide, insecticide’s active ingredients and the presence of larvae were collected and observed. Data was analyzed using chi-square analysis. The results showed that there is a wide variety of household insecticide used by samples. Most of the samples use insecticides with pyrethroid as it active ingredients. From the chi-square analysis, we concluded that there is no relationship between the various household insecticides to the presence or the absence of Aedes aegypti larvae in South Jakarta.